THE HISTOLOGICAL INVESTIGATION OF GINGIVA FROM PATIENTS WITH CHRONIC-RENAL-FAILURE, RENAL-TRANSPLANTS, AND PERIODONTITIS - A LIGHT AND ELECTRON-MICROSCOPIC STUDY - YAMALIK, N; DELILBASI, L; GULAY, H; CAGLAYAN, F; HABERAL, M; CAGLAYAN, G (AMER ACAD PERIODONTOLOGY, 1991)
THE CLINICAL AND HISTOLOGICAL APPEARANCE Of gingiva was evaluated in renal transplant recipients (RTR) receiving immunosuppressive drugs, in patients with chronic renal failure (CRF) undergoing hemodialysis, and systemically healthy individuals with periodontitis. Although the amount of bacterial plaque accumulation was similar among the groups (P > 0.05), the gingival inflammation was significantly less in RTR when compared to the other 2 groups (P < 0.05). In light microscopic investigation the overall appearance of the connective tissue was similar in all of the groups. A mononuclear cell infiltration was present in all of the specimens; however, the number of inflammatory cells in patients with periodontitis was significantly higher than the other 2 groups (P < 0.05). Prominent epithelial changes in the superficial layers of the oral epithelium; i.e., areas showing desquamation-like appearance, were noticed in patients with CRF. In electron microscopic investigation, fibroblasts and plasma cells with well-developed granular endoplasmic reticulum were found in connective tissue in RTR patients. In patients with CRF, epithelial cells presented swollen granular endoplasmic reticulum cisternae resembling vacuoles, indicating the presence of degeneration. It was suggested that with the use of immunosuppressive drugs the response to bacterial plaque did not diminish completely.
Keywords: UREMIA; RENAL TRANSPLANTATION, GINGIVAL ANATOMY AND HISTOLOGY; IMMUNOSUPPRESSANTS ADVERSE EFFECTS; IMMUNOSUPPRESSIVE DRUGS; DISEASE; INFLAMMATION; THERAPY; Dentistry, Oral Surgery & Medicine